VACCINES: THE FUTURE OF BIOTECHNOLOGY - Rakhmatullayev, Islom; Esonova , Gulnoza; O‘ralov , Abdumannon (Scientific practical conference, 2025)
This thesis discusses the pivotal role of vaccines as one of the greatest achievements of modern medicine, emphasizing their contribution to the prevention of infectious diseases, enhancement of global public health, and potential application against cancer and autoimmune disorders. It highlights the evolution of vaccine technologies from traditional approaches to advanced biotechnological methods, such as genetic engineering, recombinant DNA, and mRNA platforms. The study provides a systematic overview of vaccine types—including whole-microbe, subunit, and nucleic acid vaccines—and explains their mechanisms of action. Furthermore, it explores additional vaccine components such as preservatives, stabilizers, surfactants, residuals, diluents, and adjuvants, with particular attention to their safety and effectiveness. Overall, the thesis demonstrates how vaccines not only safeguard human health but also represent a promising future direction in biotechnology.